Contribution to the mechanical performance of a simply supported lightweight concrete beam reinforced with bio-sourced nanocomposites - Khetir, Hafid; Benfrid, Abdelmoutalib; Bachir Boiuladjra, Mohamed; Melati, Lakhder (Revista Brasileira de Engenharia de Biossistemas, 2026)
Gypsum is an essential building material widely used in the construction industry, particularly in the form of lightweight concrete. Nanotechnology has facilitated the enhancement of its properties in recent years by incorporating nanostructured materials from biological sources, such as nanoparticles derived from cow bones and African and Brazilian reeds, known for their superior mechanical properties. This study explores ways to improve the mechanical properties of lightweight concrete composites using nanoparticles from plants or animals. The goal is to enhance the bending performance of lightweight gypsum beams while aiming to reduce production costs by utilizing bio-sourced materials. We used the Mori-Tanaka method to examine the effectiveness of mixing lightweight concrete with nanometric additions from biological sources. The study of beam behavior depends on methods used in continuum mechanics, particularly bending analysis. The beams studied are simply supported. The results show that nanoparticles from bovine bones, African reed, or Brazilian reed not only strengthen the material but also significantly improve the bending performance of lightweight gypsum beams when subjected to bending.